Histological evaluation of the gut associated lymphoid tissues (GALT) of small intestine of three-month-old calves - Saw, Po Po; Abu Bakar @ Zakaria, Md Zuki; Saad, Mohd Zamri; Omar, Abdul Rahman; Abd Wahid, Mohd Effendy (Universiti Putra Malaysia Press, 2004)
Three calves of three-month-old were used in this study. The calves were slaughtered and the samples of small intestine were taken for histological evaluation. The dome epithelium of Peyer’s Patches (PPs) consisted of columnar cell, lack of goblet cells, numerous lymphocytes and a few plasma cells. The dome epithelium (lymphoepithelium) invagination was found in the discrete PPs (DPPs) of duodenum. The dome epithelium protruded into the intestinal lumen and often gave a cylindrical with rounded or conical upper ends. Dome epithelium of jejunal PPs was more superficially located in the mucosa in comparison with the ileum. The duodenal and jejunal DPPs were characterized by relatively large domes and interfollicular areas. The ileal continuous PPs (CPPs) had small domes and poorly developed interfollicular area and corona. Some dome areas of ileal PPs were composed of more collagen fibers than lymphocytes and plasma cells. The distribution of lymphoid follicles within the PPs of jejunum was significantly (p<0.05) higher than other parts of small intestine. The size of ileal lymphoid follicles was significantly (p<0.05) larger than those of other sites of small intestine.